ANALISIS KINERJA PEMERINTAH KECAMATAN DALAM PELAYANAN PUBLIK DIKECAMATAN BONE KABUPATEN BONE BOLANGO PROPINSI GORONTALO - Walangitan, Olivia Fransiske (Sam Ratulangi University, 2014)
Abstract The quality of public services from government bureaucracy very fall from expectation specially seen by the aspects accountability, responsibility, orientation of services, and effective services. The thing among others showed with still to neglectful service user importance in implementation public services. Based on problem background has been analyzed, then can formulate the problem how performance of government sub district Bone in public services. Based on problem formulation then direction of research to know how performance of government sub district Bone in public services and to identification the determine factors of government’s performance. This research treated and analyzed with use descriptive-analytic technique. Data source or respondent in this research is any civil servant in the sub district Bone office and the peoples, data source took with random sampling until sum the sample in this research 80 peoples. Result data analyzed to give a conclusion that the service unsure from apparatus performance sub district Bone is good but not optimal. Keywords : public service, government’s performance